2015
DOI: 10.1002/ejoc.201500682
|View full text |Cite
|
Sign up to set email alerts
|

Postfunctionalization of the BODIPY Core: Synthesis and Spectroscopy

Abstract: In this review we describe the various new methodologies for synthetic postmodification of the BODIPY core designed and developed by our research groups, as well as their electronic spectroscopic properties. We discuss the different strategies created for functionalization of the BODIPY framework at the pyrrole C‐ring positions and the meso‐position. Halogenated boron dipyrrins are substrates for nucleophilic substitution or Pd‐catalyzed cross‐coupling reactions. α‐Unsubstituted BODIPYs can be functionalized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
178
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 283 publications
(181 citation statements)
references
References 125 publications
(157 reference statements)
0
178
3
Order By: Relevance
“…[10][11] Recent advances in organic synthesis have expanded the possibilities of controlled modification of the BODIPY moiety, including substitution by tailored groups at every position of the core. 12 The direct conjugation of fused π-systems, extended π-bonds, the addition of alkyl or aryl groups, or the insertion of electron withdrawing or donating substituents have different effects on the spectroscopic and photophysical properties of the resulting dyes [fluorescence quantum yield () and lifetime (), absorption and emission energies (abs and em), Stokes shift ( ), full width at half maximum of the absorption and emission band (fwhmabs and fwhmem), etc.]. For instance, fusing rigid -conjugated carbocycles to the BODIPY core results in near-infrared emitting dyes.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11] Recent advances in organic synthesis have expanded the possibilities of controlled modification of the BODIPY moiety, including substitution by tailored groups at every position of the core. 12 The direct conjugation of fused π-systems, extended π-bonds, the addition of alkyl or aryl groups, or the insertion of electron withdrawing or donating substituents have different effects on the spectroscopic and photophysical properties of the resulting dyes [fluorescence quantum yield () and lifetime (), absorption and emission energies (abs and em), Stokes shift ( ), full width at half maximum of the absorption and emission band (fwhmabs and fwhmem), etc.]. For instance, fusing rigid -conjugated carbocycles to the BODIPY core results in near-infrared emitting dyes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, the BODIPY core can be postfunctionalized easily (at the pyrrole carbons, the meso-carbon and the boron atom), leading to dyes with custom-made, fine-tuned spectroscopic properties for use in bioscience and material research. 5 The transition and heavy metal ions of which the fluorometric/spectrophotometric detection is investigated are Cd The same research group also reported a selective sensor for imaging Cd 2+ in living cells, using the BODIPY scaffold (K d is ca. 60 μM), but with the DPA chelator attached at the 3-position through a p-styryl spacer (Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of fluorine could enhance the emission quantum yield further [5]. In this contribution, the title crystal structure was built up from C 19 H 18 B 2 F 3 N 2 with three title molecules in the asymmetric unit.…”
Section: Discussionmentioning
confidence: 99%
“…The title compound was synthesized according to the literature procedures [4,5]. The colorless crystals of the title compound were obtained by slow evaporation of a dichloromethane solution at room temperature.…”
Section: Source Of Materialsmentioning
confidence: 99%